(untitled) (Revista de Artes Marciales Asiáticas, 2012)
Falls in the elderly can cause injuries that lead to loss of independence. Loss of postural sway, balance, and slower reaction times are strong predictors of falling (Lajoie & Gallagher, 2004). Traditional exercise programs focus on studying and treating these factors (Tideiksaar, 1997); however, fear of falling – another strong predictor of falls – has received relatively little attention in the treatment literature (Maki et al., 1991). There are indications of a direct link between fear of falling, and actual falls (Myers et al., 1996), and a relationship between fear-related avoidance of activities and falling (Delbaere et al., 2004). Taijiquan, an ancient Chinese martial art turned exercise regimen (Wolf et al., 2001), has been shown to be effective ameliorating fear of falling and traditional antecedents of falling (Tsang et al., 2004). Like graded exposure therapies, Taijiquan practitioners slowly and progressively achieve increasingly difficult postures that simulate potentially fearful situations in a calming environment. Relative to other exercise treatments, such as computerized balance training, education, and graded exercise, Taijiquan has produced significant reductions in fear of falling and in actual falls (McGibbon et al., 2005). Herein the available research on Taijiquan and falls is reviewed to advocate for Taijiquan as a form of graded exposure therapy to reduce fear of falling and falls in seniors. Implications and future research directions will be discussed.